Las competencias emocionales en el proceso de enseñanza-aprendizaje en los niños de 7mo año de educación básica de la escuela "F.A.E." de la comunidad de San Juan de Llullundongo de la parroquia Guanujo, cantón Guaranda, provincia Bolívar en el periodo lectivo 2024-2025. - Acosta Arcos, Ronnie Sebastián (2025)
This research addresses the relationship between emotional competencies and the teachinglearning process in seventh-grade students at the “F.A.E”, academic year. Using a mixed-methods approach, the study identifies and analyzes the students’ levels of emotional development and their impact on academic performance, school participation, and social interaction. The results show that the integration of pedagogical strategies aimed at strengthening emotional competencies significantly enhances learning quality, school climate, and students’ holistic development. A set of pedagogical recommendations is proposed to promote emotionally conscious education in the classroom.